Secularizing the sacred : aspects of Israeli visual culture - Mishory, Alec (Brill, 2019)
"As historical analyses of Diaspora Jewish visual culture blossom in quantity and sophistication, this book analyzes 19th-20th-century developments in Jewish Palestine and later the State of Israel. In the course of these approximately one hundred years, Zionist Israelis developed a visual corpus and artistic lexicon of Jewish-Israeli icons as an anchor for the emerging "civil religion." Bridging internal tensions and even paradoxes, artists dynamically adopted, responded to, and adapted significant Diaspora influences for Jewish-Israeli purposes, as well as Jewish religious themes for secular goals, all in the name of creating a new state with its own paradoxes, simultaneously styled on the Enlightenment nation-state and Jewish peoplehood"-- Provided by publisher.
Keywords: Art, Israeli -- History -- 20th century.; Art, Modern -- 19th century -- History.; Jewish art and symbolism -- Israel.; Jewish art and symbolism -- Palestine.; Zionism in art.; Art israélien -- Histoire -- 20e siècle.; Art -- 19e siècle -- Histoire.; Symbolisme juif -- Israël.; Symbolisme juif -- Palestine.; Sionisme dans l'art.; Art, Modern; Art, Israeli; Jewish art and symbolism; Zionism in art; Israel; Middle East -- Palestine; 1800-1999; History